New Skin for an Old Ceremony: The Gay Revolution and the Formation of Israeli Heteroactivism - Rothschild, Leehee (ACME, 2023)
This article employs heteroactivism as a frame of analysis to examine recent shifts in resistances to gender and sexual equalities in Israel. Using ethnographic, visual, and textual methods, I examine as case studies the oppositions to two academic conferences, Issues in Therapy with Polyamory and Queer Utopias, that were both held at Bar Ilan University in 2019. The oppositions, which were led by three organisations affiliated with the Religious Zionist public (Leeba; Shovrot Shivion; Boharim Bamishpacha) reveal how Israeli heteroactivist discourses invoke familism, pro-natalism, religious sentiments, Zionist narratives, and collective trauma, in their attempts to recentralise the heteronormative Jewish family. LGBT equality in Israel has been achieved through legislative court-rulings, instead of being legally secured by the parliament, as it was in other countries previously explored by research on heteroactivsim. Nevertheless, this article shows, how this quasi-equality, combined with public sentiments of growing acceptance, induced by homonationalist and homonormative trends, sufficed to create a fertile ground for heteroactivist resistances. Through a discussion of the symbolic meaning of Bar Ilan University as an academic institution, affiliated with the Religious Zionist public, this article also illustrates how heteroactivist resistances may be embedded in specific localities and events, and not just on grand national campaigns.